PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN PADA AMSTIRDAM COFFEE DI MALANG - Reno - Maulidio; Anis Dwiastanti (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2022)
This study aims to analyze the partial and simultaneous influence of Product Quality and Price on Customer Loyalty and analyze the greatest influence between Product Quality and Price on Customer Loyalty at Amstirdam Coffee. This research is a survey research, with a descriptive approach. The population in this study were customers of Amstirdam Coffee. The sample size using Ferdinand's technique, which was taken by 108 people through purposive sampling. The results showed that there was a partial and simultaneous influence between product quality and price on customer loyalty, and product quality became the dominant variable on customer loyalty.